Analysis of Some Biochemical Properties of Recombinant Siberian Roe Deer - Murashkin, Denis E; Belenkaya, Svetlana V; Bondar, Aleksandr A; Elchaninov, Vadim V; Shcherbakov, Dmitrii N (Biochemistry (Moscow), 2023)
Structure of the chymosin gene of Siberian roe deer (Capreolus pygargus) was established for the first time and its exon/intron organization was determined. Coding part of the chymosin gene of C. pygargus was reconstructed by the Golden Gate method and obtained as a DNA clone. Comparative sequence analysis of the roe deer, cow, and one-humped camel prochymosins revealed a number of amino acid substitutions at the sites forming the substrate-binding cavity of the enzyme and affecting the S4 and S1' + S3' specificity subsites. Integration vector pIP1 was used to construct a plasmid pIP1-Cap in order to express recombinant roe deer prochymosin gene in CHO-K1 cells. CHO-K1-CYM-Cap pool cells were obtained, allowing synthesis and secretion of recombinant prochymosin into the culture fluid. As a result of zymogen activation, a recombinant roe deer chymosin was obtained and its total milk-clotting activity was estimated to be 468.4 ± 11.1 IMCU/ml. Yield of the recombinant roe deer chymosin was 500 mg/liter or [almost equal to]468,000 IMCU/liter, which exceeds the yields of genetically engineered chymosins in most of the expression systems used. Basic biochemical properties of the obtained enzyme were compared with the commercial preparations of recombinant chymosins from one-humped camel (Camelus dromedarius) and cow (Bos taurus). Specific milk-clotting activity of the recombinant chymosin of C. pygargus was 938 ± 22 IMCU/mg, which was comparable to that of the reference enzymes. Non-specific proteolytic activity of the recombinant roe deer chymosin was 1.4-4.5 times higher than that of the cow and camel enzymes. In terms of coagulation specificity, recombinant chymosin of C. pygargus occupied an intermediate position between the genetically engineered analogs of B. taurus and C. dromedarius chymosins. Thermostability threshold of the recombinant roe deer chymosin was 55°C. At 60°C, the enzyme retained <1% of its initial milk-clotting activity, and its complete thermal inactivation was observed at 65°C.